Guest molecular guided syntheses of 2-dimensional uranyl complexes with rigid benzenedicarboxylate ligands. Issue 2 (17th January 2023) - Wu, Hong-Yan; Luo, Ju-Xiang; Li, Hao-Hong; Zhang, Jian-Han
Abstract: Two new heterometallic uranyl-organic frameworks (UOFs), [Cd(phen)2 (H2 O)2 ][(UO2 )2 (BDC)3 ]·2H2 O (1 ) and [Ni(phen)3 ][(UO2 )2 (BDC)3 ]·2H2 O (2 ), were obtained under hydrothermal conditions. Both crystal structures were characterized by single-crystal X-ray diffraction analyses and the results indicate that both complexes feature a similar 2D honeycomb framework that is connected by rigid benzenedicarboxylate (BDC) ligands and uranyl units. BDC works as a linker to bridge neighboring UO2 2+ units, where UO2 2+ is tris-chelated. Different guest molecules guided the stacking of 2D layers and lead into their 3D supramolecular crystal structures with different space groups. As a result, 1 crystallized in a polar space group Cc, whereas 2 belongs to a chiral space group P 61 22. Thermogravimetric measurements were performed to study their thermal stability. UV-visible diffuse reflectance spectroscopy measurements indicate an experimental optical bandgap of 3.87 eV and 3.63 eV, respectively, for 1 and 2 . Luminescent studies of both samples show strong green light emissions. Abstract : UF0001